Gorlin Syndrome: Assessing Genotype-Phenotype Correlations and Analysis of Early Clinical Characteristics as Risk Factors for Disease Severity. Issue 19 (1st July 2022) - Betancourt, Nicolas J.; Qian, Mollie F.; Pickford, Jean R.; Bailey-Healy, Irene; Tang, Jean Y.; Teng, Joyce M.C.
Abstract : PURPOSE: Gorlin syndrome (GS) is a rare genetic disorder characterized by lifetime risk of basal cell carcinomas (BCCs), skeletal anomalies (SAs), and other extracutaneous neoplasms. There is great variation in disease severity, and a genotype-phenotype correlation has not been well established. Here, we investigate whether patients' clinical characteristics predict disease severity to inform clinical decision making. METHODS: Data of 248 patients with GS were collected between 2014 and 2021 from three institutions. Multivariable regression analyses were performed to investigate whether clinical characteristics predicted disease burden. Genotype-phenotype correlations were investigated in 40 patients. RESULTS: Patients with SAs had a mean increase of 120 lifetime BCCs (95% CI, 27.1 to 213) relative to patients without SAs. Those with ≥ 2 SAs had 2.45 increased odds (95% CI, 1.01 to 5.91) of advanced or metastatic BCCs. Moreover, the presence of multiple SAs was associated with 5.00 increased odds of having a keratocystic odontogenic tumor (95% CI, 2.22 to 11.3) and 2.79 increased odds of an ovarian fibroma (95% CI, 1.05 to 7.40). Genotype-phenotype analyses showed that missense/in-frame mutations were more likely to be hereditary compared with severe deleterious mutation types (100% v 27%; P = .004). In addition, heat map visualization illustrated that those with more deleterious variants, like large deletions, trended toward increased burden of SAs and BCCs per year. CONCLUSION: GS patients with SAs may be at greater risk for developing more numerous and severe BCCs and other neoplastic growths including keratocystic odontogenic tumors and ovarian fibromas. Current clinical guidelines suggest yearly follow-up in individuals with GS. Since SAs are usually recognized at the time of diagnosis, our results suggest that more vigilant lifetime multidisciplinary surveillance should be considered for these patients starting in childhood. Abstract :